Personas tiesības prasīt atlīdzību no Ārstniecības riska fonda par kaitējumu, kas nodarīts mantojuma atstājējam - Bovkune, Anastasija (Latvijas Universitāte, 2019)
Bakalaura darbā “Personas tiesības prasīt atlīdzību no Ārstniecības riska fonda par kaitējumu, kas nodarīts mantojuma atstājējam” ir apskatītas Ārstniecības riska fonda darbības noteikumu 3.1 un 15.2. punkti kopsakarā ar Pacientu tiesību likuma 16.pantu pirmo daļu ar mērķi noteikt personu loku, kas var saņemt atlīdzību no Ārstniecības riska fonda par kaitējumu, kas tika nodarīts pacientam. Darba ietvaros tiek pētīta administratīvo tiesu prakse par personu subjektīvajām tiesībām uz morāla kaitējuma atlīdzību, tiesu prakse mantojuma tiesībās un kaitējuma atlīdzības jautājumos. Tiek analizēti Satversmes tiesas spriedumi, juridiski zinātniska literatūra un judikatūra. Autore analīzē normatīvo aktu interpretācijas un piemērošanas problēmas, identificē to cēloņus un piedāvā savu risinājumi.

Bachelor's work "The individual's right to seek reimbursement from the Medical Risk Fund for the damages caused to the deceased" looks at the Medical Risk Fund clauses 3.1 and 15.2 in conjunction with the first part of Article 16 of the Patient Rights Act with the purpose of determining the range of people who may receive compensation from the Medical Treatment Fund for damages to the patient, their rights and obligations. The work of the Administrative Courts on subjective rights of individuals to participate in the process and compensation for moral damages, the practice of civil law courts in the matter of inheritance law and compensation for damages have been studied. Judgments of the Constitutional Court were analyzed. Legal scientific literature and case laws have been studied. The author analyses problems of interpretation and application of regulatory enactments identifies their causes and offers her solutions to these problems. Keywords: Medical Treatment Risk Fund, heirs, damage to life and health, patients' rights law, patient, individual.
The individual's right to seek reimbursement from the Medical Risk Fund for the damages caused to the deceased
Keywords: Juridiskā zinātne; Ārstniecības riska fonds; mantinieki; kaitējums veselībai un dzīvībai; pacientu tiesību likums; pacients